Inhalation of electronic cigarettes slightly affects lung function and inflammation in mice - Dai, Yuxing; Duan, Kun; Huang, Guangye; Yang, Xuemin; Jiang, Xingtao; Chen, Jianwen; Liu, Peiqing (Frontiers in Toxicology, 2023)
Electronic cigarettes have become increasingly popular, but the results of previous studies on electronic cigarette exposure in animals have been equivocal. This study aimed to evaluate the effects of electronic cigarette smoke (ECS) and cigarette smoke (CS) on lung function and pulmonary inflammation in mice to investigate whether electronic cigarettes are safer when compared to cigarettes. 32 specific pathogen-free BALB/c male mice were randomly grouped and exposed to fresh air (control), mint-flavored ECS (ECS1, 6 mg/kg), cheese-flavored ECS (ECS2, 6 mg/kg), and CS (6 mg/kg). After 3 weeks exposure to ECS or CS, we measured lung function (PIF and Penh) and blood oxygen saturation. The levels of TNF-α and IL-6 in the bronchoalveolar lavage fluid (BALF) and serum were measured using ELISA. HE staining was performed to observe the pathological changes in the lung tissues. The levels of IL-6 in BALF and serum, and TNF-α in BALF, were elevated similarly in the ECS and CS groups compared to the control group. Significant elevation was observed in serum TNF-α levels in the CS group. The total count of cells in BALF were increased after ECS1 exposure and CS exposure. PIF and oxygen saturation decreased, and Penh increased markedly in the CS group but not in the ECS groups. Compared with the ECS groups, mice in the CS group had widened lung tissue septa and increased inflammatory cell infiltration. However, we did not detect significant differences between mint-flavored and cheese-flavored e-cigarettes in our study. Overall, our findings suggested that both ECS and CS impair lung function and histopathology while promoting inflammation. In contrast, ECS has a less negative impact than CS.